The tadpole of Hypsiboas pombali (Caramaschi, Pimenta & Feio, 2004) (Anura, Hylidae) - Juncá, Flora Acuña; Camurugi, Felipe; de Almeida Mercês, Ednei (Zootaxa, 2012)
Hypsiboas pombali is, on the basis of its morphological similarity to H. semilineatus (Caramaschi et al. 2004), one of the six species of the clade H. semilineatus group (Faivovich et al. 2005). Here, we described the external morphology of the previously unknown tadpole of Hypsiboas pombali.